Hubungan antara Kepatuhan Minum Obat dengan Kualitas Hidup Penderita Tuberkulosis - Ritassi, Aloysia Juniarti; Nuryanto, I Kadek; Rismawan, Made (Jurnal Gema Keperawatan, 2024)
The period of tuberculosis treatment affects patient compliance with the treatment. Compliance to medication is a very important indicator of success for the recovery of tuberculosis patients which can lead to changes in the patient's health status which affects the quality of life of tuberculosis patients. To identify the correlation between compliance in taking medication and the quality of life of tuberculosis patients in the working area of Labuan Bajo Public Health Center. This study employed a correlation analytic study with a cross sectional approach. The study was conducted from August 2023 to January 2024 in the working area of Labuan Bajo Public Health Center. The population in this study were all patients with tuberculosis. 80 people involved in this study selected through total sampling. The data were collected using a questionnaire to measure their compliance in taking medication, and the WHOQOL-BREFF quality of life questionnaire. The collected data were then analyzed using Pearson Product Moment test. The results of study showed that the majority of tuberculosis patients had a high quality of life (81.3%) and comply in taking medication (77.5%). The results of the analysis showed a significant correlation between compliance in taking medication and the quality of life of tuberculosis patients in the working area of Labuan Bajo Public Health Center (p0.05, r=0.67). Family support plays an important role in improving the quality of life of patients. The lack of knowledge about the medicine side effect lead to incompliance in taking medication.